Gray squirrel alarm call composition differs in response to simulated aerial versus terrestrial predator attacks. Issue 1 (2nd January 2017) - McRae, T.R.; Green, S.M.
Abstract : Eastern gray squirrels use three acoustically distinct vocalizations, namely kuks, quaas and moans, in their alarm calling bouts. Although moans are highly specific to aerial threats, kuks and quaas show no clear association with either terrestrial or aerial predator type when simply examining their presence or absence in an entire bout of vocal signaling. Here we examine the relationship between alarm call composition (the presence and rate of kuks, quaas and moans) and the type of stimulus eliciting the alarm call (aerial or terrestrial). When the first 30 sec or second 30 sec of calling is examined, the presence of kuks, quaas (only used in the second 30-sec period), and moans are all associated with stimulus type. Kuks and quaas are usually used in response to terrestrial stimuli and moans are used exclusively in response to aerial stimuli. The relationship between call composition and stimulus is even stronger when considering the rate of calls. In the first 60 sec of calling, all three vocalizations differ in rate depending on threat type, with more kuks and more quaas elicited by terrestrial than aerial stimuli, while moans are not produced at all with terrestrial stimuli. Overall rates of calling, combining all three vocalization types, also differed by stimulus type. The median number of vocalizations in the first 60 sec of calling bouts elicited by terrestrial threats was nearly 3 times greater than in calling bouts elicited by aerial threats. The alarm calls of gray squirrels are predator-specific, containing significant information on whether a threat is aerial or terrestrial. Further, the rate of each vocalization type in the initial 60 sec of calling bouts provides more information than does only the presence or absence of each vocalization type.